CONSTITUTIONAL PRACTICE OF ASEAN COUNTRIES: QUESTIONING JUDICIAL REVIEW, RELIGIONS AND MINORITY ISSUES - Muhammad Siddiq Armia (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2022)
ASEAN countries vary in culture and ethnicity, and these differences affect the way states are run. In respecting the spirit of democracy and also part of constitutional practice, those countries have frequently amended their constitutions. ASEAN countries have adopted numerous models of constitutional practice from the post-colonial era. The need to re-examine and re-evaluate existing rules to make them relevant to common and indigenous models and value systems has led to a consistent renewal and review of existing models. Looking the systems ASEAN countries have utilized when implementing their constitutions, there are three models of constitutional practice: the Westminster Model, Socialist Model, and Mixed Model. Abstrak: Negara-negara ASEAN memiliki budaya dan keragaman etnis yang mempengaruhi cara bernegara. Negara-negara di kawasan ini memiliki konstitusi yang energik dan bergerak menyesuaikan waktu. Dalam menghormati semangat demokrasi dan praktik ketatanegaraan, negara-negara di ASEAN acapkali melakukan amandemen konstitusi. Negara-negara ASEAN telah memiliki banyak model praktik ketatanegaraan yang diadopsi dari era penjajahan. Sekarang, negara-negara di ASEAN telah melakukan pembaruan yang konsisten, dengan mengevaluasi kembali aturan yang ada untuk menjadikannya relevan dengan model dan sistem nilai yang berlaku umum. Melihat sistem negara-negara ASEAN yang menerapkan konstitusinya, dapat disimpulkan ada tiga model praktik ketatanegaraan yang terjadi di ASEAN; pertama adalah Model Westminster, Model Sosialis, dan Model Campuran. Ketiga model ini mempengaruhi cara pengujian undang-undang, penanganan isu-isu agama dan minoritas.Kata Kunci: Konstitusi ASEAN, Judicial Review, Isu Agama dan Minoritas